Low-temperature solid oxide fuel cells based on Tm-doped SrCeO2-δ semiconductor electrolytes. (June 2021) - Rauf, S.; Zhu, B.; Shah, M.A.K.Y.; Tayyab, Z.; Attique, S.; Ali, N.; Mushtaq, N.; Asghar, M.I.; Lund, P.D.; Yang, C.P.
Abstract: Low-temperature solid oxide fuel cells (LT-SOFCs) are a promising fuel cell technology but often suffer from low ionic conductivity of the electrolyte. Herein, we develop a solid electrolyte with high ionic conductivity based on thulium (Tm)-doped composite Sr0.1 Tmx Ce0.9-x O2-δ [x = 0.1] having a cubic fluorite structure. The fuel cell using Tm-doped SrCeO2-δ electrolyte achieved the power output of 682 mW/cm 2 at 550 °C with an open-circuit voltage (OCV) of 1.03 V, whereas the fuel cell with Sr0·1 Ce0·9 O2-δ electrolyte produced a power density of 515 mW/cm 2 with an OCV of 1.02 V. Doping of 10% Tm into SrCeO2-δ enables the creation of oxygen vacancies in the structure, which enables the enhancement in ionic conductivity and provides the fast transport path. Thus, doping of both Sr and Tm into CeO2 enhances the generation of high content of oxygen vacancies. The calculated ionic conductivity of Tm-doped SrCeO2-δ is 0.13 S/cm which is appreciably higher than that of the pure SrCeO2-δ (0.104 S/cm at 550°C). Moreover, the enhancement of power output can also be ascribed to band bending at the electrolyte-electrode interface, which overall decreases the inherent electronic properties of reduced ceria while increases the ionic conductivity. Graphical abstract: Image 1 Highlights: Developed a novel single-phase Tm-doped SrCeO2-δ  electrolyte. A doping strategy was applied to design a new semiconductor electrolyte into LT-SOFCs. Achieved high ionic conductivity and remarkable fuel cell performance at 550°C.